Um estudo de caso sobre servitização e nacionalização em um fabricante de hardware elétrico - Bromberg, Adalberto Tadeu de Oliveira (2015)
This thesis has as main caractheristics, the research, analysis and the proposal of a model that considers the most relevant factors for the inclusion of the services’ process in manufacturing based companies, especially for companies seeking the nationalization its supply basis. Within this concept of transition and incorporation of services, which is known in the literature as 'servitization', and using as a research subject one electrical hardware manufacturer, it was assessed the planning and execution of servitization for offshore technical services, related to the supply chain of the Subsea Oil and Gas Production industry segment. To support the understanding on the company in regards to services and sertitization and support this research, it was necessary to review the literature on Operations Management in Services, Product - Service Systems, Servitization, Lean Thinking in Services, Products and Services Project Development and Local Content Requirements. Based on the documentation provided by the company, and comparing it with the reviewed academic literature, it was found that the models proposed by the literature do not contain all the elements required to directly apply them on such business. Based on this assessment, it is found the most relevant elements for servitization and it is proposed a model for reflection, which fullfils most specifically the gaps that negatively influence the operational excelance and the corporate strategy of a company related to the Oil and Gas industry.